Axial Compression Behaviour Of Cross Laminated Wood-Wool Cement Composite Panel Wallettes Bonded With Lightweight Cement Mortar - Ali, Mohammad Farhan; Md Noh, Mohammad Soffi (Recent Trends in Civil Engineering and Built Environment, 2021)
As a building and housing component, WWCP has outstanding potential because it resists biological degradation and has excellent heat and noise insulation capabilities. In the construction industry, it is very difficult to find a new sustainable wall production that is not dependent on non-renewable construction materials. In order to maintain a sustainable environment and to improve living conditions, it is important to find a new alternative in this sector. The main research objectives are to determine strength properties of lightweight cement mortar and investigate the axial compression behaviour of cross laminated wood-wool cement composite panel wallettes bonded with lightweight cement mortar. WWCP of 50 mm thickness, lightweight cement mortar and A6 wire mesh were used. For the fabrication of wallettes, the panel were laid in two layers to form a 900 mm x 900 mm wallettes, with different orientation of panel arrangement where front and rear panel were arranged in the longitudinal and transverse direction. The panel were bonded together by using lightweight cement mortar of 15 mm to form approximately 115 thick wall and inserted with A6 wire mesh. Three sample of wallettes were fabricated in this studies to determine the average value. Initially, the density, flexural and compressive strength of lightweight cement mortar were determined after 28 days age according to BS EN 1015‑11:2019 and axial compression test were conducted to determined the load capacity of wallettes. The results indicated that the wallettes have an ability to sustained maximum axial compression load of 102 kN. This show that the application of lightweight mortar used as bonding agent together with A6 wire mesh have a great potential in fabrication of wood-wool cement composite wallettes.